Stained glass window detail - Ghosh, Ayan (Jio Institute, 2023)
Another architectural feature common between the BMC building and CSMT is the extensive use of stained-glass windows. They depict various themes linked to the evolution of Mumbai under the British Empire, for example, in this window, the wooden ship is symbolic of the maritime trade that brought wealth and colonial administration to the city.